Case Book for Diploma in Hospital Dental Practice (DHDP) - Bangamuarachchi, S.I (My University, 2005)
Surgical removal of impacted mandffiular tidrd molar; One visit root canal treatment for non vital maxillary central incisor; A case of radicular cyst in left side maxilla; Multiple tooth extraction in a haemophilia b patient; Providing a complete denture for an edentulous patient; Mucous extravasation cyst in lower lip; Correction of anterior crossbite ' using a removable appliance; Light activated composite for restoration of carious teeth; Management of a case of oral lichen planus; management of salivary calculi in submandffiular duct